Cross-sectional associations of different types of nature exposure with psychotropic, antihypertensive and asthma medication. Issue 2 (16th January 2023) - Turunen, Anu W; Halonen, Jaana; Korpela, Kalevi; Ojala, Ann; Pasanen, Tytti; Siponen, Taina; Tiittanen, Pekka; Tyrväinen, Liisa; Yli-Tuomi, Tarja; Lanki, Timo
Abstract : Background: Exposure to natural environments is thought to be beneficial for human health, but the evidence is inconsistent. Objective: To examine whether exposure to green and blue spaces in urban environments is associated with mental and physical health in Finland. Methods: The Helsinki Capital Region Environmental Health Survey was conducted in 2015−2016 in Helsinki, Espoo and Vantaa in Finland (n=7321). Cross-sectional associations of the amounts of residential green and blue spaces within 1 km radius around the respondent's home (based on the Urban Atlas 2012), green and blue views from home and green space visits with self-reported use of psychotropic (anxiolytics, hypnotics and antidepressants), antihypertensive and asthma medication were examined using logistic regression models. Indicators of health behaviour, traffic-related outdoor air pollution and noise and socioeconomic status (SES) were used as covariates, the last of these also as a potential effect modifier. Results: Amounts of residential green and blue spaces or green and blue views from home were not associated with medications. However, the frequency of green space visits was associated with lower odds of using psychotropic medication (OR=0.67, 95% CI 0.55 to 0.82 for 3–4 times/week; 0.78, 0.63 to 0.96 for ≥5 times/week) and antihypertensive (0.64, 0.52 to 0.78; 0.59, 0.48 to 0.74, respectively) and asthma (0.74, 0.58 to 0.94; 0.76, 0.59 to 0.99, respectively) medication use. The observed associations were attenuated by body mass index, but no consistent interactions with SES indicators were observed. Conclusions: Frequent green space visits, but not the amounts of residential green or blue spaces, or green and blue views from home, were associated with less frequent use of psychotropic, antihypertensive and asthma medication in urban environments.